2017
DOI: 10.1108/ejim-04-2017-0041
|View full text |Cite
|
Sign up to set email alerts
|

The innovation capacity of small food firms in Italy

Abstract: Purpose The purpose of this paper is to analyze the innovation capacity of small and medium enterprises (SMEs) and micro enterprises through a theoretical framework that addresses the influence of some internal and external resources – derived from the literature review – on the development of innovation activities and on innovative firm’s results. Design/methodology/approach Based on a structured questionnaire, the empirical survey has involved 122 SMEs and micro enterprises of the most representative agrif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 40 publications
1
55
2
2
Order By: Relevance
“…; Maietta ; Caiazza and Stanton ; Ciliberti et al . ,b; De Martino and Magnotti ; Sauer ; Wixe et al . ).…”
Section: Resultsunclassified
See 4 more Smart Citations
“…; Maietta ; Caiazza and Stanton ; Ciliberti et al . ,b; De Martino and Magnotti ; Sauer ; Wixe et al . ).…”
Section: Resultsunclassified
“…In this study, small businesses that sought debt and/or equity finance were found significantly more likely to innovate. The lack of financial resources suffered by small agri‐food firms influenced innovation, but public funding can boost their innovation capacity (Caiazza and Stanton ; and De Martino and Magnotti ). This result shows the need of small food businesses in Australia for continued government assistance to help sustain their innovation activities.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations